The Tuberculosis Program: A Managerial Epidemiology Perspective - Litelnoni, Aletha; Kleden, Simon Sani; Wahyuni, Maria M. D.; Kambuno, Norma Tiku; Batubara, Sakti Oktaria (Jurnal Pangan Gizi dan Kesehatan, 2026)
Background: Tuberculosis (TB) remains a global health problem, including in Indonesia. The East Nusa Tenggara Province Health Center (SITB) reported 10,110 TB cases (56%) in 2024. Tuberculosis (TB) remains a significant public health problem in Indonesia, including in Kupang Regency, East Nusa Tenggara Province. The gap between the estimated number of TB cases and the cases that were successfully detected and reported indicates that there are still various challenges in implementing TB control programs at the regional level. These challenges relate to managerial aspects, resource availability, health care systems, and community involvement. Objective: This study aims to describe the implementation of the tuberculosis program from a managerial epidemiology perspective in Kupang Regency in 2025. Methods: This study used a descriptive research design. Data were obtained through in-depth interviews with TB program managers at primary and referral health care facilities. Results: The results of the study indicate that the implementation of the TB program in Kupang District has not been optimal in almost all managerial and service components.